Integrated business development - Carina Koppers; Matthias Klumpp (MA Akademie Verlags- und Druck-Gesellschaft mbH, 2010)
Business Development traditionally has an incorporated focus on marketing and marketing models as well as marketing competencies among business development managers. However, the discussed case studies results and trends in business and market behaviour point to the fact that in the future only an integrated model of business development (including logistics, supply and quality management models and activities, respectively personnel) can provide significant competitive advantages especially to global companies. This is described in detail in the following paper and put together as an integrated business development model in order to enhance practical efficiency efforts and results in day to day business development.
Keywords: 650; Unternehmenswachstum; Erfolgsfaktor; Qualitätsmanagement; Humanressourcen; Logistik; Organisationsforschung; Theorie